Determining the effect of Foreign Direct Investment (FDI), Export, and External debt on Gross Domestic Product in Selected ASEAN Country Periodic 2000-2014 - Kurniawan, Ruly (Jurnal Ilmiah Mahasiswa FEB, 2016)
The international trade through Foreign Direct Investment (FDI), export, and external debt  around  the  world  had  been increased  significantly  since  the  1980s.  However,  the distribution of FDI and external debt has been uneven, and there is a big gap between developed and developing countries. Many developing countries in the different region including those who joined in the ASEAN have made some effort to attract FDI, and external debt inflows by introducing policies in fiscal and financial incentives, new strategy, and so forth to enhance the economic performances and exports. Even though such policies can be effective, the benefit at the host countries may be limited in effecting their economies.Analysis was processed through data panel regression. This method is used to know the relation and affect the independent variable to dependent variables. The result of this study shows the FDI, Export, and External debt significantly affect the economic growth which shown by Adjusted-Gross Domestic Product (AdjGDP) whether simultaneously and partially.Keywords : Economic growth performance, FDI, exports, external debt.